Gender Empowerment in Sheep Fattening for Youth & Women’s Groups in Ethiopia - Wamatu, Jane; Ekule, Muluken (International Center for Agricultural Research in the Dry Areas, 2022)
A training report on gender empowerment for sheep fattening youth and women groups.